2010
DOI: 10.1371/journal.pntd.0000627
|View full text |Cite
|
Sign up to set email alerts
|

Lutzomyia Sand Fly Diversity and Rates of Infection by Wolbachia and an Exotic Leishmania Species on Barro Colorado Island, Panama

Abstract: BackgroundSand flies (Diptera, Psychodidae, Phlebotominae) in the genus Lutzomyia are the predominant vectors of the protozoan disease leishmaniasis in the New World. Within the watershed of the Panama Canal, the cutaneous form of leishmaniasis is a continuous health threat for residents, tourists and members of an international research community. Here we report the results of screening a tropical forest assemblage of sand fly species for infection by both Leishmania and a microbe that can potentially serve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
2
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 62 publications
9
96
2
13
Order By: Relevance
“…trapidoi and Lu. gomezi (Azpurua et al 2010). In the Amazonian region of Ecuador, natural infection of Lu.…”
Section: Discussionmentioning
confidence: 99%
“…trapidoi and Lu. gomezi (Azpurua et al 2010). In the Amazonian region of Ecuador, natural infection of Lu.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, different methods have been developed to screen pools or clusters of insects, which can efficiently estimate the infection potential of disease spread by a vector species (Yameogo et al 1999;Martin-Sanchez et al 2006;Bhattarai et al 2009;Severinsson, et al 2010). The rates of sand fly infection varied in accordance with the transmission of the disease, as observed in other studies reported from Panama (Azpurua et al 2010), Athens (Aransay et al 2000), and Turkey (Svobodova et al 2009). The prevalence of infection with Leishmania in the vector female P. argentipes may be exploited as a tool for the surveillance of these infections, and for measuring the success of control programs.…”
Section: Discussionmentioning
confidence: 92%
“…Molecular methods such as PCR are highly sensitive and easy to perform compared to optical microscopy. Using PCR for the detection of Leishmania has proven useful (Cabrera et al 2002;Bhattarai et al 2009;Azpurua et al 2010). This technique would be expensive and highly labor-intensive if individual insects are analyzed, as the number of sand flies collected could be in the thousands.…”
Section: Introductionmentioning
confidence: 99%
“…La detección de la infección natural de Wolbachia por la presencia de su ADN en poblaciones silvestres de insectos vectores presentes enáreas donde se reportan enfermedades infecciosas, es importante porque este endosimbionte puede ser usado como control biológico para disminuir las tasas de infección al bloquear la actividad patogénica de diversos microorganismos (virus y pará-sitos) (Ono et al, 2001;Azpurua et al, 2010;Rodriguero & Marcela, 2013;Wallace, 2013). Este estudio reporta y confirma la presencia de Wolbachia en un grupo de machos de Lu.…”
Section: Discussionunclassified